PENGARUH PERSEPSI KEGUNAAN, PERSEPSI KEMUDAHAN, KEPUASAN PENGGUNA DAN KESIAPAN TEKNOLOGI INFORMASI TERHADAP PENGGUNAAN E-FILING - Sari, Gaziela Eka; Atichasari, Anna Sofia; Ristiyana, Rida (POLITEKNIK LP3I JAKARTA, 2023)
The purpose of this research is to analyze the influence of perceived usefulness, perceived ease of use, user satisfaction and readiness of technology information towards the use of e-Filing. This research uses primary data. The respondents are an individual taxpayer who reports SPT Tahunan using e-filing and registered in the Tax Office (KPP) Madya and Pratama in Tangerang and South Tangerang City. There are 112 respondents in this study. The sampling technique used is convenience sampling. Data analysis in this research uses multiple linear regression with SPSS 25 Program. The results of this study indicate that: (1) perceived usefulness has an influence on the use of e-filing, (2) perceived ease of use has an influence on the use of e-filing, (3) user’s satisfaction has an influence on the use of e-filing, (4) readiness technology information doesn’t have an influence on the use of e-filing.Keywords: Perceived Usefulness, Perceived Ease Of Use, User’s Satisfaction, Readiness Technology Information, The Use Of E-Filing.